The Effect of Various Fertilizer Doses on Sugarcane Seed Growth and Productivity - Dony Agung Wicaksono; Deny Bagus Surendra; Febry Ari Marpaung; Nanik Tri Ismadi (Journal of Biodiversity and Biotechnology, 2025)
Fertilization plays a crucial role in promoting plant growth, increasing yield, and improving crop quality. Current fertilization recommendations for sugarcane are generally based on production-oriented cultivation with a 12-month growth period, while specific fertilization requirements for seed sugarcane remain insufficiently studied. This study aimed to determine the optimal fertilizer dosage for sugarcane seed by evaluating the effects of different fertilizer combinations on plant growth and productivity. The research was conducted at the Experimental Farm of Puslit Sukosari. The experimental area covered 0.046 ha, with planting rows 8 m in length and a row factor of 1042 rows/ha. Four fertilizer treatments were applied: (A) ZA 640 kg/ha, SP 36 48.1 kg/ha, and KCl 255 kg/ha; (B) ZA 531 kg/ha, SP 36 40 kg/ha, and KCl 213 kg/ha; (C) ZA 427.5 kg/ha, SP 36 31.9 kg/ha, and KCl 171 kg/ha; and (D) ZA 321.3 kg/ha, SP 36 23.9 kg/ha, and KCl 129 kg/ha. The results showed that increasing fertilizer dosage did not result in a linear increase in seed sugarcane productivity. The highest seed productivity and optimal growth performance, including the number of stalks, stalk height, stalk diameter, and seed weight per hectare, were obtained under Treatment B. In contrast, the lowest productivity was observed under Treatment D. Considering both fertilization efficiency and production costs during the vegetative growth phase, seed sugarcane plantations may be fertilized using the complete fertilizer combination in Treatment B or solely with nitrogen fertilizer at a rate of ZA 531 kg/ha.